# math

There is one step in a proof that I don't understand. Could someone please explain?

u = any vector in vector space S
W = finite dimensional subspace of S with orthonormal basis of vectors {v1, v2, ..., vn}

The theorem to prove is: u can be expressed exactly one way as
u = w1 + w2

w1 = orthogonal projection of u onto W
w2 = component of u orthogonal to W
w = arbitray vector in subspace W

w1 = <u,v1>*v1 + <u,v2>*v2 + ... + <u,vn>*vn
w2 = u - w1
w = k1*v1 + k2*v2 + ... + kn*vn

<w2,w> = <u - w1,w> = <u,w> - <w1,w>
<u,w> = <u,k1*v1 + k2*v2 + ... + kn*vn> = k1*<u,v1> + k2*<u,v2> + ... + kn*<u,vn>
(!!! Don't understand where this equation came from --->) <w1,w> = <u,v1>*k1 + <u,v2>*k2 + ... + <u,vn>*kn
<u,w> = <w1,w> so <w2, w> = 0

Where, did that one line come from? the textbook makes a reference to this theorem but includes no other explanation:

If S is an orthornormal basis for an n-dimensional inner product space and
us = (u1,u2,...,un)
vs = (v1,v2,...,vn)
then
<u,v> = u1v1 + u2v2 + ... + unvn

You use the fact that the inner product is bi-linear. So, you can always linearly expand. E.g.:

<c_1u_1 + c_2u_2, d_1v_1+d_2v_2> =

c_1d_1<u_1,v_1> +
c_1d_2<u_1,v_2> +
c_2d_1<u_2,v_1> +
c_2d_2<u_2,v_2> +

If you take u_i = v_i to be the i-th unit vector, then:

<u_1,v_1> = 1

<u_2,v_2> = 1

<u_1,v_2> = 0

<u_2,v_1> = 0

The vector

c_1u_1 + c_2u_2

can be denoted as

(c_1,c_2)

and

d_1v_1+d_2v_2 as

(d_1,d_2)

The inner product is

c_1d_1 + c_2d_2

because the "cross terms" vanish as they are proportional to inner products of orthogonal vectors.

w1 = <u,v1>*v1 + <u,v2>*v2 + ... + <u,vn>*vn

w = k1*v1 + k2*v2 + ... + kn*vn

and if you take the inner product between w1 and w then you get a sum of the inner products of all the combinations where you pick the i-th term from w1 and the j-th term from w, summed over i and j. But these are zero unless i = j, because <v_i,v_j> = 0 if i and j are not equal. If i and j are the same then it is 1. So, you end up with the sum of

<u,v_j>k_j from j = 1 to n.

bingo, got it! In hindsight, that's pretty simple. But, I just couldn't figure that out yesterday.

thank you so much count iblis!

1. 👍 0
2. 👎 0
3. 👁 61

## Similar Questions

1. ### Physics

I'm trying to prove Kepler's equations the proof is in my book but I don't understand it (T1/T2)^2 = (s1/s2)^3 ok first what allows us to rewrite that formula as so??? (s1^3/T1^2)=(s2^3/T2^2) my book goes about the proof as m1 ((4

asked by QUESTION on August 19, 2009
2. ### Algebra (Does any one understand special factors)?

I do not understand special factors, the teacher on Friday tried to explain in to me in class but she went so fast, and every time we complain that we don't understand it she gets mad. So could someone please help me with at least

asked by Rae Rae on April 5, 2009
3. ### Math

What is wrong with the following proof. You must explain your answer in words. a>3 3a>3(3) 3a-a^2>9-a^2 a(3-a)>(3-a)(3+a) a>3+a 0>3 the problem with the proof is that the fourth step needs the sign to be reverse...but why? i

asked by Wenny on January 26, 2008
4. ### Latin

Can someone help me to understand the step by step process of the five declensions? I don't seem to understand what makes the first only feminine, etc, etc. If someone could explain it clearly that would be great!

asked by Suomynona on February 25, 2008
5. ### AP Physics

Hello I was trying to find the proof of the formula x = x0 + v0t +.5at^2 were the zeros are subscripts My text book dosen't explain it that well. ok well it involves the formula for average velocity aver velocity = 2^-1(v0 + v)

asked by AP Physics on June 13, 2009
6. ### science

I don't fully understand this could you help? In this section, you will create a step-by-step procedure for testing and monitoring the number of trout and catfish in Cypress Pond. You must monitor them once per month for 12 months

asked by Turtle on March 10, 2019
7. ### Geometry 2020

HELP!!! I am soooo lost.... I don't understand anything....I can't really show what I am doing because it has a picture but the direction is: Show an organized proof with justification for every step. Given:Parallelogram ABCD

asked by ? on October 22, 2008

Can somebody please help me I don't understand this problem.? Determine whether each ordered pair is solution of y=x+3. 1. (2, 9) 2. (5, 23) can you please explain this to me step by step till you get the answer .thank you so

asked by jenn k on August 22, 2013
9. ### Geometry

Find the measure of angle DBC. D=X^2+1 A=2x+3x-2 C=4x+3 This is the only question I do not know for my homework ,I just don't understand it. PLEASEE Explain Step By Step .

asked by Amber on October 27, 2013
10. ### Geometry

A parabola has a focus of F(2,8.5) and a directrix of y=9.5. The point P(x,y) represents any point on the parabola, while D(x,9.5) represents any point on the directrix. Maria was asked to use the distance formula to write an

asked by lilbaby on December 4, 2018
11. ### Math

Explain how you would factor x^2-5x-24 You must explain EACH step and process t get to your factored solution The work I have done - (x-8)(x+3) I just don't understand how to explain.

asked by Kelly on April 19, 2017

More Similar Questions